2022
DOI: 10.1039/d2nr00040g
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying-assisted construction of hierarchically porous ZIF-8 for controlled release of doxorubicin

Abstract: Hierarchically porous ZIF-8 (HP-ZIF-8) and DOX@HP-ZIF-8 were efficiently fabricated by spray drying. DOX@HP-ZIF-8 exhibits ultrahigh loading and encapsulation efficiency, and the release system is pH-triggered and controlled by the mesopore size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In the drying process, aqueous ZnO and Fe 3 O 4 composite nanodispersions are rapidly atomized and dried via compressed air, and then continuously assembled into ZnO-Fe 3 O 4 HMNAs with a regular structure and good dispersity. [29][30][31] Compared with individual ZnO and Fe 3 O 4 NPs, the spray-dried HMNAs exhibit ultrahigh efficiency. The NH 3 -TPD, pyridine-adsorption IR analysis and DFT study reveal the increased Lewis acidity and enhanced adsorption of PET over HMNAs, further confirming the structural synergy effect of ZnO-Fe 3 O 4 HMNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In the drying process, aqueous ZnO and Fe 3 O 4 composite nanodispersions are rapidly atomized and dried via compressed air, and then continuously assembled into ZnO-Fe 3 O 4 HMNAs with a regular structure and good dispersity. [29][30][31] Compared with individual ZnO and Fe 3 O 4 NPs, the spray-dried HMNAs exhibit ultrahigh efficiency. The NH 3 -TPD, pyridine-adsorption IR analysis and DFT study reveal the increased Lewis acidity and enhanced adsorption of PET over HMNAs, further confirming the structural synergy effect of ZnO-Fe 3 O 4 HMNAs.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 ZIF-8 is a three-dimensional (3D) MOF with a zeolite crystal structure formed by linking zinc ions with methylimidazolate ligands, and is considered one of the best MOF materials for drug delivery due to its low biotoxicity, large porosity, antibacterial properties, and highly controlled release rate. 20,21 Research showed that ZIF-8 particles loaded with doxorubicin (DOXO) could signicantly slow down release of the DOXO. 22 Aer 30 d, the cumulative release of DOXO was only 66%.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidosomes, also known as Pickering emulsion microcapsules, have both hollow and self-assembly structures. They have extensive applications in fabrics, food, , medicine, , agriculture, and many other aspects. The conventional preparation process of colloidosomes is to assemble latex particles at the oil–water interface, and the latex particles are then locked to form shells to encapsulate the active materials. Colloidosomes can easily be functionalized depending upon the type of loaded nanoparticles with specific properties. Among these functionalized structures, magnetic nanoparticle (NP)-loaded colloidosomes can be used as carriers to trigger the release of drugs, which can be remotely controlled by an external magnetic field. , The accumulation of the drug-loaded colloidosomes is rapid in a magnetic response pathological area, which can avoid side effects to normal cells. …”
Section: Introductionmentioning
confidence: 99%